Avaliação das condições higiênico-sanitárias de abates de suínos no Estado da Paraíba - Ferreira, Valquiria Cardoso da Silva (2012)
The physical structure of slaughterhouses, sanitary-hygienic practices and microbiological parameters related to pork quality were assessed. Five slaughterhouses in the state of Paraíba were inspected, using a checklist and were classified into group I (low risk), II (intermediate risk) and III (high risk). The microorganisms investigated were: in water: total and faecal coliforms; in carcasses, handlers hands and knives: total and faecal coliforms, mesophilic aerobic bacteria, Staphylococcus aureus, and presence of Salmonella sp. in carcasses. In total and faecal coliform, mesophilic aerobic bacteria and Staphylococcus aureus counts, a completely randomized design (CRD) with five treatments and five replications was used. The slaughterhouses were classified in Group III (high risk). Although there are differences between slaughterhouses and collection points contamination levels above permitted levels for all analyses were observed, Salmonella was present in 12% of carcasses. Contamination of water and knives suggested cross-contamination.